2015
DOI: 10.1016/j.adolescence.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Raising trophy kids: The role of mothers' contingent self‐esteem in maternal promotion of extrinsic goals

Abstract: This study examined the role of mothers' child-invested contingent self-esteem, that is, their tendency to hinge their self-worth on their child's achievements, in maternal promotion of extrinsic goals, as perceived by adolescents. It was also examined whether maternal promotion of extrinsic goals would, in turn, relate to adolescents' Social Dominance Orientation (SDO). Participants were 184 mothers and their adolescent children (66% female). Maternal child-invested contingent self-esteem predicted adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
0
35
1
Order By: Relevance
“…These results are not completely aligned with previous research, which found that child-invested parental contingent self-worth was related to the use of a more controlling approach towards others (Soenens, Wuyts, Vansteenkiste, Mageau, & Brenning, 2015;Wuyts et al, 2015). Several explanations can be provided for this inconsistency.…”
Section: Discussioncontrasting
confidence: 97%
“…These results are not completely aligned with previous research, which found that child-invested parental contingent self-worth was related to the use of a more controlling approach towards others (Soenens, Wuyts, Vansteenkiste, Mageau, & Brenning, 2015;Wuyts et al, 2015). Several explanations can be provided for this inconsistency.…”
Section: Discussioncontrasting
confidence: 97%
“…Although past studies have focused mostly on goals that people have for their own achievements, research is beginning to show that in relationships people elaborate goals that concern the person with whom they are interacting and that these goals influence their behaviors toward this other person (Carbonneau and Koestner 2014;Soenens et al 2015). The present findings, together with Gonida and Cortina (2014)'s study, confirm that parents do have goals regarding their children's achievements and that these achievement goals are associated with their parenting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that adolescent’s aspirations may be linked to the aspirations of their close others (Soenens, Wuyts, Vansteenkiste, Mageau, & Brenning, 2015), as well as to the degree to which their parents are autonomy‐supportive (Kasser, Koestner, & Lekes, 2002). However, such claims have been under‐researched, and focus primarily on the role of mothers and usually in Western, non‐individualistic countries.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we test the associations between fathers’ and adolescents’ own intrinsic and extrinsic aspirations and the well‐being of both fathers and their adolescent children (for example, to what extent does fathers’ relative intrinsic aspiring link to the basic psychological needs of their children). There is considerable evidence to suggest that aspirations affect one’s own well‐being (Kasser & Ryan, 1993, 1996, 2001), and some evidence to suggest that one’s own aspirations relate to the aspirations of close others (Soenens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%